Alcohol and fatal life trajectories in Russia: understanding narrative accounts of premature male death in the family - Leon David A; Bobrova Natalia; Keenan Katherine; Saburova Lyudmila; Elbourne Diana (BMC, 2011)
Abstract Background In the post-Soviet period, Russian working-age men have suffered unusually high mortality rates. Earlier quantitative work found that part of this is attributable to hazardous and harmful patterns of alcohol consumption, which increased in the period of transition at a time of massive social and economic disruption and uncertainty. However, there has been very little work done to document and understand in detail the downward life trajectories of individual men who died prematurely from alcohol-related conditions. Building on an earlier case-control study, this unique qualitative study investigates the perceived interplay between men's drinking careers, their employment and family history, health and eventual death. Methods In-depth interviews were conducted with close relatives (most often the widow) of 19 men who died between 2003 and 2005 aged 25-54 years whose close relatives reported that alcohol contributed to their death. The study was conducted in a typical medium-sized Russian city. The relative's accounts were analysed using thematic content analysis. Results The accounts describe how hazardous drinking both contributed to serious employment, family and health problems, and was simultaneously used as a coping mechanism to deal with life crises and a decline in social status. The interviews highlighted the importance of the workplace and employment status for shaping men's drinking patterns. Common themes emerged around a culture of drinking in the workplace, peer pressure from colleagues to drink, use of alcohol as remuneration, consuming non-beverage alcohols, Russian-specific drinking patterns, attitudes to treatment, and passive attitudes towards health and drinking. Conclusions The study provides a unique insight into the personal decline that lies behind the extremely high working-age mortality due to heavy drinking in Russia, and highlights how health status and hazardous drinking are often closely intertwined with economic and social functioning. Descriptions of the development of drinking careers, hazardous drinking patterns and treatment experiences can be used to plan effective interventions relevant in the Russian context.